Image reproduction with compensation of luminance adaptation. Issue 1 (January 2017) - Celikcan, Ufuk; Arpa, Sami; Capin, Tolga
Abstract We introduce an image reproduction model that retargets colors for printing purposes to ensure similar luminance perception under photopic and scotopic vision. Our model is based on the physiological functioning of the rod and cone cells in the retina in varying lighting conditions, so that the human visual system exhibits responses akin to a printed output of the model for different illumination levels. Prior to retargeting, digital color images are converted to spectral representations and their photopic and scotopic luminance responses are obtained. The color retargeting is realized by optimizing our compensation function over the color space. In addition, we present a spatially varying operator to enhance the color coherence over salient regions. Reproduction results demonstrate substantially decreased difference between the two luminance responses. Further, it is validated through psychophysical evaluation that our model on average provides superior recognition rates in dark environments, while keeping the noticeable differences in aesthetic appeal acceptable in well-lit environments.